Beginning teachers and teaching work in the period of social isolation due to covid-19: searching for possibilities in impossibilities - Wegrzyn Magrinelli Martinez, Flavia (2022)
This article presents the results of a qualitative-quantitative research carried out with 84 novice teachers working in Basic Education and Higher Education, from 15 Brazilian states. The study aimed to understand the experiences of these teachers about teaching work in the period of social isolation due to Covid-19. To obtain the data, a questionnaire made available via Google Forms on social network was used. For the codification and quantitative organization of the collected data, we used IRAMUTEQ, a free software that is developed under the logic of open source. It is a statistical environment anchored in R software and python programming language. In this study, we used the similarity analysis based on the frequency of words and on the theory of graphs, making it possible to identify the co-occurrences between the words and possible relationships between the terms. For qualitative data analysis, the Content Analysis (Bardin, 2016) was used. The research reveals that aspects related to teacher deprofessionalization were intensified in the pandemic. It also allowed us to verify that teachers, moved by political and ethical commitment, are moving towards an action that proposes to overcome what is offered or denied in terms of working conditions. The participating teachers acted with the (im) possibilities and (un) predictability that presented themselves in the school (and outside) and established a possible path.